Is Automation Labor-Displacing in the Developing Countries, Too? Robots, Polarization, and Jobs - Maloney, William F. (World Bank, Washington, DC, 2020)
This paper uses global census data to examine whether the labor market polarization and labor-displacing automation documented in the advanced countries appears in the developing world. While confirming both effects for the former, it finds little evidence for either in developing countries. In particular,the critical category corresponding to manufacturing worker, operators and assemblers has increased in absolute terms and as a share of the labor force. The paper then uses data on robot usage to explore its impact on the relative employment evolution in each sample controlling for Chinese import penetration. Trade competition appears largely irrelevant in both cases. Robots, however, are displacing in the advanced countries, explaining 25-50 percent of the job loss in manufacturing. However, they likely crowd in operators and assemblers in developing countries. This is likely due to off-shoring that combines robots with new operators in FDI destination countries which may, for the present, offset any displacement effect. Some evidence is found, however, for incipient polarization in Mexico and Brazil.